The effect of a severe health shock on work behavior: Evidence from different health care regimes. (July 2015) - Datta Gupta, Nabanita; Kleinjans, Kristin J.; Larsen, Mona
Abstract: In this paper, we use the policy variation of two different types of health insurance in the US and in Denmark – employer-provided and universal insurance combined with substantial differences in expected and actual medical out-of-pocket expenditures – to explore the effect of new severe health shocks on the labor force participation of older workers. Our results not only provide insight into how relative disease risk affects labor force participation at older ages, but also into how different types of health care and health insurance systems affect individual decisions of labor force participation. Although employer-tied health insurance and greater out-of-pocket medical expenditures give US Americans greater incentives to continue to work, we find only small differences in the work response between the two countries. We provide compelling evidence that our somewhat counterintuitive finding is the result of differential mortality and baseline health differences coupled with distinct treatment regimes under the respective health care systems. Highlights: The effect of severe health shocks on the work response of the elderly is explored. Data consist of US HRS (1994–2002) and a 20% Danish register sample (1993–2001). We find few country differences in the work response after a health shock. Danish men are nearly 3 times more likely to die from new cancer than US men. Differences in treatment regimes and in baseline health can explain this finding.